A Stand Structure and Composition and Model for Estimating Stand Volume Potential at the Citragaluh Sustainable Community Forest Management Unit, Subang Regency, West Java - Wilhelmus Medhavi; Tien Lastini; Endang Hernawan (School of Life Sciences and Technology, Institut Teknologi Bandung, 2023)
In general, community forest management is still limited to the management of individual farmers so that it affects diversity, especially in the form of stands. This study aimed to explore the stand structure and composition characteristics and develop a model for estimating the potential stand volume at the Citragaluh community forest management unit with 55 observation plots based on a combination of slope and density classes. The data taken includes slope; plant species; plant coordinates; planting pattern and spacing; tree diameter, tree height, and canopy density. The results of plot observations showed that the cropping pattern of Citragaluh Community Forest Management Unit (CFMU) consisted of monoculture (10.9%), mixed stands (20%), agroforestry (29%), dry fields (27.27%), wet fields (9%), bamboo stands (1.8%) and built-up area (1.8%). The trees species found were Jeungjing, Mahogany, Teak, Tisuk, Sobsi, Akasia, and Puspa. Based on the results of stratification, diameter distribution, and stand volume, mixed gardens were the best cropping pattern. This research proves the role of community forest as a transition between plantation forest and natural forest based on the stand form and composition. The stand volume potential estimator model chosen was linear with the equation Y = 0.074X1 + 2.924 X2 - 1.679 where X1 = slope and X2 = Normalized Difference Vegetation Index (NDVI). The values of R2 models are 51.3%. The average potential for the Citragaluh is 119,835 m3/ha, which tends to be higher than other community forest studies.